The Bathtub Illusion. (July 2019) - Bertamini, Marco
When a person looks at the fingers of their own hand as they line up in depth, the impression may emerge that the little fingers, which are farther away, are located too far and if so they are not part of the same hand. I describe the conditions and suggest this is due to the size difference between fingers (size-distance scaling). A role of size on perceived distance here is more powerful than knowledge about our own body.